Embryonic development of hematopoietic stem cells: implications for clinical use. (May 2012) - Clapes, Thomas; Robin, Catherine
Hematopoietic stem cell (HSC) transplantation is an important treatment modality for hematological malignancies or to correct congenital immunodeficiency disorders. Several stem cell sources are currently applied clinically, with a recent increased application of umbilical cord blood. The low number of HSCs available, particularly in umbilical cord blood, is a limiting factor, and different lines of research are ongoing to circumvent this issue. In this review, we will describe the research strategies developed to expand adult HSCs in vitro and to generate new HSCs from pluripotent stem cell lines. We will also discuss the importance of studying the embryonic microenvironment since it allows both generation and extensive expansion of HSCs. Understanding the mechanisms that underlie HSC production, self-renewal and differentiation is necessary for the establishment of optimal in vitro HSC cultures, where a limitless and manipulatable resource of HSCs would be available for both clinical and fundamental research.